2017
DOI: 10.1177/1362361317712650
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing psychiatric comorbidity in children with autism spectrum disorder receiving publicly funded mental health services

Abstract: Publicly funded mental health programs play a significant role in serving children with autism spectrum disorder. Understanding patterns of psychiatric comorbidity for this population within mental health settings is important to implement appropriately tailored interventions. This study (1) describes patterns of psychiatric comorbidity in children with autism spectrum disorder who present to mental health services with challenging behaviors and (2) identifies child characteristics associated with comorbid con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
94
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 132 publications
(104 citation statements)
references
References 68 publications
9
94
1
Order By: Relevance
“…The rates and patterns of probable concomitant psychiatric disorders observed in this sample were similar to those reported in children with ASD receiving publicly-funded mental health services 12 . The high rates of ODD and CD in children with ADHD have been observed in the general pediatric population and in children with ASD 14, 10 .…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…The rates and patterns of probable concomitant psychiatric disorders observed in this sample were similar to those reported in children with ASD receiving publicly-funded mental health services 12 . The high rates of ODD and CD in children with ADHD have been observed in the general pediatric population and in children with ASD 14, 10 .…”
Section: Discussionsupporting
confidence: 75%
“…The prevalence estimates for all anxiety disorders are likely understated because specific phobia was not included. The high co-occurrence of ADHD and anxiety disorders in youth with ASD was also observed by Brookman-Frazee et al (2017) 12 . In the general pediatric population, by contrast, the review by Angold et al (1999) 14 reported significantly lower co-occurrence of ADHD and anxiety disorders compared to the association between ADHD and ODD/CD.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations